A Game-Based Learning Application to Help Learners to Practice Mathematical Patterns and Structures - Lozano, Adrian S.; Canlas, Reister Justine B.; Coronel, Kimberly M.; Canlas, Justin M.; Duya, Jerico G.; Macapagal, Regina C.; Dungca, Ericson M.; Miranda, John Paul P. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The purpose of this study is to develop a game-based mobile application to help learners practice mathematical patterns and structures. Method – The study followed a mixed-method research design and prototyping methodology to guide the study in developing the mobile application. An instrument based on the Octalysis framework was developed as an evaluation tool for the study. Results – The study developed a mobile application based on the Octalysis framework. The application has fully achieved all its intended features based on the rating provided by the students and IT experts. Conclusion – The study successfully developed a mobile learning application for mathematical patterns and structures. By incorporating GBL principles and the Octalysis framework, the app achieved its intended features and received positive evaluations from students and IT experts. This highlights the potential of the app in promoting mathematical learning. Recommendations – This study recommends that the application be further enhanced to include other topics. Incorporating other game-based principles and approaches like timed questions and the difficulty level is also worth pursuing. Actual testing for end-users is also needed to verify the application's effectiveness. Practical Implications – Successful development of a game-based mobile app for practicing mathematical patterns and structures can transform education technology by engaging learners and enhancing their experience. This study provides valuable insights for future researchers developing similar applications, highlighting the potential to revolutionize traditional approaches and create an interactive learning environment for improving mathematical abilities.